Whole-body sodium-mri at 3 T using an asymmetric birdcage resonator and short echo time sequence: first images of a male volunteer - Wetterling, Friedrich (My University, 2012)
Sodium magnetic resonance imaging (²³Na MRI) is a non-invasive technique which allows spatial resolution of the tissue sodium concentration (TSC) in the human body. TSC measurements could potentially serve to monitor early treatment success of chemotherapy on patients who suffer from whole body metastases. Yet, the acquisition of whole body sodium (²³Na) images has been hampered so far by the lack of large resonators and the extremely low signal-to-noise ratio (SNR) achieved with existing resonator systems. In this study, a ²³Na resonator was constructed for whole body ²³Na MRI at 3T comprising of a 16-leg, asymmetrical birdcage structure with 34 cm height, 47.5 cm width and 50 cm length. The resonator was driven in quadrature mode and could be used either as a transceiver resonator or, since active decoupling was included, as a transmit-only resonator in conjunction with a receive-only (RO) surface resonator. The relative B₁-field profile was simulated and measured on phantoms, and 3D whole body ²³Na MRI data of a healthy male volunteer were acquired in five segments with a nominal isotropic resolution of (6 × 6 × 6) mm³ and a 10 min acquisition time per scan. The measured SNR values in the ²³Na-MR images varied from 9 ± 2 in calf muscle, 15 ± 2 in brain tissue, 23 ± 2 in the prostate and up to 42 ± 5 in the vertebral discs. Arms, legs, knees and hands could also be resolved with applied resonator and short time-to-echo (TE) (0.5 ms) radial sequence. Up to fivefold SNR improvement was achieved through combining the birdcage with local RO surface coil. In conclusion, ²³Na MRI of the entire human body provides sub-cm spatial resolution, which allows resolution of all major human body parts with a scan time of less than 60 min.
PUBLISHED